The Integrating Prophetic Ethics into Modern Commerce: A Case Study of Justice, Transparency, and Sustainability in Indonesia - Cholyfah Ayu Nuraeny; Tiara Supinah; Sumarta; Faiz Musthofa Abbas (Lentera Peradaban: Journal on Islamic Studies, 2025)
This research examines the implementation of the values of justice in the trading practices of Prophet Muhammad (PBUH) and their relevance to the contemporary Islamic economy in Indonesia. The study is motivated by the urgent need to integrate Islamic ethical principles (such as honesty (shiddiq), trustworthiness (amanah), transparency, and social responsibility) into modern economic practices that face challenges like economic inequality, monopolies, and low ethical awareness. This study employs a qualitative approach using library research and content analysis, examining the Qur’an, Hadith, fiqh muamalah literature, scientific journals, and research reports related to Islamic business ethics. A qualitative descriptive analysis was conducted to understand the application of justice in income distribution, risk management, and socio-economic mechanisms such as mudharabah, musharakah, zakat, and waqf. The results indicate that Prophet Muhammad (PBUH) consistently upheld the value of justice in every economic transaction, creating a trading system that was fair, transparent, and harmonious for traders, consumers, and society alike. These values remain highly relevant to contemporary Islamic economic instruments, supporting social gap reduction, community welfare, and business sustainability. Challenges to implementation include resistance from business actors, a lack of public understanding, and inadequate regulations; thus, successful adaptation requires synergy between the government, business practitioners, and society. Practically, the principle of justice can be applied across traditional markets, modern retail, and e-commerce through transparency, equitable profit distribution, risk management, and the integration of productive zakat and waqf, thereby building an inclusive, fair, and sustainable economic ecosystem.